The Penal System Is a Mirror of Social Injustice: The Debts with Women in Prison - Palma Campos, Claudia (2019)
This article aims to analyze the context where the criminal system occurs, which enables the application of certain regulations. It also analyzes the moral and cultural notions of the implementation of these regulations, as well as the commission of a crime, specifically concerning women in jail. It is based on the author's direct experience as an anthropologist and feminist in Costa Rica's prisons, mainly working with women deprived of their liberty for almost ten years. This paper tries to look at the social place that women have occupied and how this is reflected when they arrive in prison, how they can be looked at and treated and how their crimes, their punishments, and their claims are the product, in one way or another, of inequality and social injustice reflected in criminal injustice. There is a discussion about different experiences in the penal system in Costa Rica, and serious problems are formulated that reinforce social inequality, such as sexism and lack of a gender approach. In conclusion, women in prison are not different from other socially oppressed women in the country. Their voices, their needs, and their sorrows belong to the same order as those that, day by day, try to devise ways to belong, socially, economically and politically, to a country that has denied them opportunities. It is proposed as an obligation to retake their voices to contribute to social equity.